2020
DOI: 10.4081/ejtm.2020.8982
|View full text |Cite
|
Sign up to set email alerts
|

Increase of resting muscle stiffness, a less considered component of age-related skeletal muscle impairment

Abstract: Elderly people perform more slowly movements of everyday life as rising from a chair, walking, and climbing stairs. This is in the first place due to the loss of muscle contractile force which is even more pronounced than  the loss of muscle mass. In addition, a secondary, but not negligible, component is the rigidity or increased stiffness which requires greater effort to produce the same movement and limits the range of motion of the joints. In this short review, we discuss the possible determinants of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…In old age, there is a loss of muscle mass and alterations to the structural components of the neuromuscular system, impairing contractile function and performance (Power et al, 2013), and there appears to be elevated passive tension for a given muscle length (Marcucci and Reggiani, 2020). Ageing muscles of rodents and humans undergo structural remodelling, whereby muscle fascicle lengths become shorter than in the young (Hooper, 1981;Narici et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In old age, there is a loss of muscle mass and alterations to the structural components of the neuromuscular system, impairing contractile function and performance (Power et al, 2013), and there appears to be elevated passive tension for a given muscle length (Marcucci and Reggiani, 2020). Ageing muscles of rodents and humans undergo structural remodelling, whereby muscle fascicle lengths become shorter than in the young (Hooper, 1981;Narici et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Pavan et al (2020) noted no age-related differences at the single-fibre level, but the passive tension of fibre bundles from old humans was greater than that of young humans across all sarcomere lengths, as a result of collagen-induced stiffening of the extracellular matrix. It is important to note that, at the joint level, older adults have greater musculotendinous stiffness (Ochala et al, 2004;Marcucci and Reggiani, 2020), and experience an earlier increase in passive force for a given joint rotation (Gajdosik et al, 2004) than that experienced by young. At the whole-muscle and joint level, muscle architecture contributes relatively more to understanding contractile function than do single-fibre properties (Narici et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, VR was beneficial for both healthy young adults and older adults. The literature review performed by Marcucci et al indicated that a decline in older adults' joint ROM is associated with changes in their joints, muscles, tendons, and fasciae [18]. More specifically, joint changes include cartilage degeneration, joint capsule thickening, and ligament stiffness increases; muscle and tendon changes include muscle stiffness increases and tendon stiffness decreases; and fascia changes include stiffness increases [18].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review performed by Marcucci et al indicated that a decline in older adults' joint ROM is associated with changes in their joints, muscles, tendons, and fasciae [18]. More specifically, joint changes include cartilage degeneration, joint capsule thickening, and ligament stiffness increases; muscle and tendon changes include muscle stiffness increases and tendon stiffness decreases; and fascia changes include stiffness increases [18]. Given that the effects of aging on joint ROM occur simultaneously in joints, muscles, tendons, and fasciae, we expected the effectiveness of VR in older adults to be less than that in young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation